Evaluating the Validity of Gold Futures Trading in Light of DSN-MUI Fatwa No. 77/2010 - Sylvia Ayu Amara Putri; Afthon Yazid; Adamu Abubakar Muhammad (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2025)
This study aims to evaluate the practice of gold futures trading at PT. Agung Cindo Berjangka and assess its compliance with the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) No. 77/DSN-MUI/V/2010 regarding non-cash gold transactions. The problem identified in this research is the misalignment between trading practices and Islamic legal provisions, which raises concerns about the validity of such transactions from a Sharia perspective. Utilizing a qualitative field research method and a case study approach, data were collected through interviews, observations, and documentation. The findings indicate that the trading practices involve contract-based transactions that do not entail physical gold delivery, thereby contradicting several key provisions in the DSN-MUI Fatwa No. 77. Specifically, the study highlights violations of the clause prohibiting price increases during the contract period and the presence of gharar (uncertainty), maysir (speculation), and riba (usury). These elements render the practice non-compliant with Sharia principles and Islamic economic ethics.